2016
DOI: 10.2147/ndt.s120496
|View full text |Cite
|
Sign up to set email alerts
|

The role of heme oxygenase-1 (HO-1) in the regulation of inflammatory reaction, neuronal cell proliferation and apoptosis in rats after intracerebral hemorrhage (ICH)

Abstract: ObjectiveTo investigate the role of heme oxygenase-1 (HO-1) in the regulation of inflammatory reaction, neuronal cell proliferation and apoptosis in rats after intracerebral hemorrhage (ICH).MethodsThirty-six adult Sprague Dawley (SD) male rats were randomly divided into sham operation, ICH and zinc protoporphyrin (ZPP) group. Rats (except for the sham operation group) were given 50 μL stereotactic injection of autologous blood from the femoral artery into the caudate nucleus, to establish an ICH model. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…There is an antioxidant response element in its promoter region, which is regulated by Nrf2 [ 30 ]. HO-1 directly affects the antioxidative balance in the body, and it has anti-inflammatory and antiapoptotic activities as well [ 31 , 32 ]. Moreover, GPF administration not only induced Nrf2 expression but also promoted Nrf2 transfer from the cytoplasm to the nucleus in PC12 cells, in a dose-dependent manner ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is an antioxidant response element in its promoter region, which is regulated by Nrf2 [ 30 ]. HO-1 directly affects the antioxidative balance in the body, and it has anti-inflammatory and antiapoptotic activities as well [ 31 , 32 ]. Moreover, GPF administration not only induced Nrf2 expression but also promoted Nrf2 transfer from the cytoplasm to the nucleus in PC12 cells, in a dose-dependent manner ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…HO-1, which is regulated by Nrf2, has been recently considered to be important against ischemic brain injury [39]. It directly affects the antioxidative balance in the body, and it has antiapoptotic activities as well [40]. Importantly, the ability to promote Nrf2/HO-1 protein expression and Nrf2 nuclear translocation of UA was significantly blocked after preadministration of brusatol, suggesting that UA may regulate ARE-related gene expression through promoting Nrf2 activation to play antioxidative effects after FCI/R.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 protein family is a key regulator of apoptosis and Bax can promote apoptosis while Bcl-2 can inhibit apoptosis, with ratio changes of Bcl-2/Bax directly reflecting the level of apoptosis [ 40 , 41 ]. When stimulated by upstream apoptosis signal, the initiation factors of caspase-8 and caspase-9 are cleaved and activated by other kinases, and the apoptosis signal is then transmitted to the cascade execution factor caspase-3 to induce apoptosis [ 42 ]. The results in the present work suggested that effects of exposure to PM 2.5 during pregnancy on the development of cerebral cortex in mice offspring could be achieved by up-regulating the expressions of Caspase-3, Caspase-8, and Caspase-9, and down-regulating the expression of Bcl-2.…”
Section: Discussionmentioning
confidence: 99%